2021
DOI: 10.1002/ps.6685
|View full text |Cite
|
Sign up to set email alerts
|

The combination of two Bacillus strains suppresses Meloidogyne incognita and fungal pathogens, but does not enhance plant growth

Abstract: BACKGROUND The combination of biocontrol agents is a desirable strategy to improve control efficacy against the root‐knot nematode (RKN) Meloidogyne incognita under field conditions. However, strains compatibility is generally tested in vitro and incompatible combinations are normally not further examined in experiments in planta. Therefore, there is virtually no information on the performance of incompatible strains. In this study, we evaluated two Bacillus strains previously described as incompatible in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…It has been previously reported that bacterial consortia are more effective at controlling certain fungal pathogens than single bacterial strains [ 56 , 57 ]. In this study, B. velezensis BTS-4 and the Bacillus consortium performed better than the other Bacillus treatments in suppressing MoT mycelial growth and conidial germination in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that bacterial consortia are more effective at controlling certain fungal pathogens than single bacterial strains [ 56 , 57 ]. In this study, B. velezensis BTS-4 and the Bacillus consortium performed better than the other Bacillus treatments in suppressing MoT mycelial growth and conidial germination in vitro.…”
Section: Discussionmentioning
confidence: 99%